Leaf stomatal conductance and stomatal morphology of Musa germplasm - Ekanayake, I.J.; Ortíz, R.; Vuylsteke, D.R. (1998)
Drought tolerance combined with resistance to black sigatoka (BS) disease are two desirable traits for plantains in some parts of the tropics. Field evaluation of leaf stomatal conductance, single leaf transpiration rate, photochemical efficiency, and role of stomata in BS resistance, was done for 18 genotypes of Musa spp., which included diploid and triploid banana and plantains and tetraploid plantain hybrids, at a subhumid and a humid site. Conductances were significantly (P≤0.01) higher for leaf abaxial than adaxial surfaces (S), while clonal (C) differences were significant (P≤0.05). Interactions between sampling period (T: morning vs afternoon) and location (L), and clone and location (C x L) were significant for both conductance and transpiration; (C x T x L) interaction was significant for conductance. Significant interactions for (C _ L) and (C _ T) suggested that conductance and transpiration of a specific clone need to be considered for a given environment. Total variation in conductance was explained by the following variables: S, C, (C x L), (C x T), and (C x L x T). In general, ABB cooking banana had higher conductances than other Musa taxonomic groups (AAB, AA, AAA, and AAAB). Evaluation of morphological and physiological traits of leaf stomata indicated that the resistance to BS disease is due to nonstomatal mechanisms